Efficacy of acupuncture for the treatment of Parkinson’s disease-related constipation (PDC): A randomized controlled trial - Li, Ying-Jia; Leong, Ian-I; Fan, Jing-Qi; Yan, Ming-Yue; Liu, Xin; Lu, Wei-Jing; Chen, Yuan-Yuan; Tan, Wei-Qiang; Wang, Yu-Ting; Zhuang, Li-Xing (Frontiers in Neuroscience, 2023)
Objective: To evaluate the efficacy of acupuncture in treating Parkinson's disease-related constipation (PDC). Methods: This was a randomized, controlled trial in which patients, outcome assessors, and statisticians were all blinded. Seventy-eight eligible patients were randomly assigned to either the manual acupuncture (MA) or sham acupuncture (SA) groups and received 12 sessions of treatment over a 4-week period. Following treatment, patients were monitored until the eighth week. The primary outcome was the change in weekly complete spontaneous bowel movements (CSBMs) from baseline after treatment and follow-up. The Constipation Symptom and Efficacy Assessment Scale (CSEAS), the Patient-Assessment of Constipation Quality of Life questionnaire (PAC-QOL), and the Unified Parkinson’s Disease Rating Scale (UPDRS) were used as secondary outcomes. Results: In the intention-to-treat analysis, 78 patients with PDC were included, with 71 completing the 4-week intervention and 4-week follow-up. When compared to the SA group, weekly CSBMs were significantly increased after treatment with the MA group (P<0.001). Weekly CSBMs in the MA group were 3.36 (standard deviation [SD]1.44) at baseline and increased to 4.62 (SD,1.84) after treatment (week 4). The SA group's weekly CSBMs were 3.10 (SD,1.45) at baseline and 3.03 (SD,1.25) after treatment, with no significant change from baseline. The effect on weekly CSBMs improvement in the MA group lasted through the follow-up period (P <0.001). Conclusion: Acupuncture was found to be effective and safe in treating PDC in this study, and the treatment effect lasted up to 4 weeks.